PENGEMBANGAN BAHAN AJAR MEMBACA PERMULAAN BERBASIS PERMAINAN DI SD - Fitriah Erza Nurrohmah; Djuanda, Dadan; Iswara, Prana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early reading instruction in elementary schools still uses conventional methods that tend to be monotonous, making them less effective in increasing student motivation and engagement. This study aims to develop game-based early reading instructional materials that are engaging, interactive, and appropriate to the characteristics of elementary school students. The study employed the Design and Development (D&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects were first and second grade elementary school students, with the instructional materials divided into letter level for first grade and word level for second grade. The validation results from material experts obtained a final percentage of 87.5%, categorized as very feasible, while the validation results from media experts obtained a final percentage of 95%, categorized as very feasible. The implementation showed positive student responses with a percentage of more than 90% in the very good category, and teacher responses were also in the very good category in all assessment aspects. The evaluation resulted in minor revisions to instructions, vocabulary, layout, and color, making the media more communicative and engaging. Thus, the game-based early reading instructional materials are declared feasible and effective for use in learning, and can be an alternative innovation for basic literacy media in elementary schools.